Green Urine Secondary to Propofol (Revista de Medicina Clinica, 2023)
Clinical Snapshot on "Green Urine Secondary to Propofol" presented in volume 7 issue 3 of 2023 of Revista de Medicina Clínica.
Keywords: Urine; Green; Propofol